Design of a New Propulsion Mechanism of Imitating Duck’s Webbed-feet - Yuan Dai; Zhongqiang Zheng; Jinlei Chen; Zongyu Chang (Institute of Advanced Engineering and Science, 2013)
With the wide application of the underwater vehicle in ocean exploration, bionics propulsion aroused intensive interest among researchers. Bionic locomotion of aquatic animals has the advantages of highly maneuver, power-efﬁcient endurance and so on. In the paper the mechanism of duck’s swimming is studied and a novel bionics propulsion mechanism is designed and analyzed. The mechanics of underwater vehicle is investigated by ADAMS. Dynamics response of the system is analyzed by using numerical method. The simulation results suggest that the designed propulsion mechanism can imitate the movement modes of the duck’s webbed feet, and implement the motion of vehicle in fluid environment. DOI: http://dx.doi.org/10.11591/telkomnika.v11i8.3133